High-Residue Cultivation Timing Impact on Organic No-Till Soybean Weed Management. (20th March 2017) - Zinati, Gladis M.; Seidel, Rita; Grantham, Alison; Moyer, Jeff; Ackroyd, Victoria J.; Mirsky, Steven B.
Abstract : A cereal rye cover crop mulch can suppress summer annual weeds early in the soybean growing season. However, a multi-tactic weed management approach is required when annual weed seedbanks are large or perennial weeds are present. In such situations, the weed suppression from a cereal rye mulch can be supplemented with the use of high-residue cultivators which can prolong the weed-free period during soybean growth. Research trials were conducted to determine the optimum timing of high-residue cultivation for weed control in rolled-crimped cereal rye mulches. Treatments included three cultivation timings with a high-residue cultivator: early (3-4 wk after soybean planting (WAP)), intermediate (5-6 WAP), and late (7-8 WAP), a weed-free and no-cultivation control. Crop and weed measurement included cereal rye biomass, weed biomass, soybean population and biomass, and yield. Cereal rye biomass was 50% lower and weed biomass was three times greater in 2011 than in 2010 and 2012 due to 2011 being a dry year. There was no significant effect of cultivation timing on soybean population when compared to no-cultivation or hand-weeded treatments. While cultivation reduced weed biomass by 67% compared to no-cultivation, soybean yield was only improved by 12% in early and late cultivation treatments and 22% in intermediate cultivation treatment when compared to no-cultivation. Effective strategies for improving weed management by integrating the use of a high-residue cultivator in no-till organic systems could help existing organic field crop producers to reduce tillage while also encourage adoption of organic crop production by conventional growers who prefer reduced-tillage systems. Unlike traditional organic cultivation equipment, therefore, optimal timing of cultivation should be delayed several weeks in organic cover crop-based no-till planted soybean production as compared to the typical tillage-based approach to ensure both weed control and optimal yield. Abstract : Los residuos de un cultivo de cobertura de centeno pueden suprimir malezas anuales de verano temprano durante la temporada de crecimiento de la soja. Sin embargo, se requiere un manejo de malezas con tácticas múltiples cuando el banco de semillas de malezas anuales es grande o malezas perennes están presentes. En tales situaciones, la supresión de malezas por parte de los residuos del centeno pueden ser complementados con el uso de cultivadores especiales para condiciones de altos residuos, lo cuales pueden prolongar el período libre de malezas durante el crecimiento de la soja. Se realizaron ensayos de investigación para determinar el momento óptimo para cultivar con el objetivo de controlar malezas en residuos de centeno cortados y aplastados con rodillo (rolled-crimped) que formaron un acolchado sobre el suelo. Los tratamientos incluyeron tres momentos de cultivo con un cultivador para altos residuos: temprano (3−4 semanas después de la siembra de la soja (WAP)), intermedio (5−6 WAP), y tarde (7−8 WAP), un testigo libre de malezas y un testigo sin cultivo. Las mediciones del cultivo y de malezas incluyeron biomasa del centeno, biomasa de malezas, y biomasa, población y rendimiento de la soja. La biomasa del centeno fue 50% menor y la biomasa de las malezas tres veces mayor en 2011 que en 2010 y 2012 debido a que el 2011 fue un año seco. No hubo un efecto significativo del momento del cultivo sobre la población de la soja cuando se comparó con los tratamientos sin cultivo y con deshierba manual. Mientras que el cultivar redujo la biomasa de las malezas en 67% al compararse con el tratamiento sin cultivo, el rendimiento de la soja fue solamente mejorado en 12% en los tratamientos con cultivo temprano y tarde y 22% con el tratamiento con cultivo intermedio, cuando se compararon con el tratamiento sin cultivo. Estrategias efectivas para la mejora del manejo de malezas que integren el uso de un cultivador para altos residuos y sistemas orgánicos con cero labranza podrían ayudar a productores orgánicos de cultivos extensivos existentes a reducir la labranza mientras que también se promueve la adopción de producción orgánica de cultivos por parte de productores convencionales quienes prefieren sistemas de labranza reducida. A diferencia de cuando se usan equipos tradicionales de labranza para sistemas orgánicos, en sistemas de cero labranza para la producción de soja que incorporan cultivos de cobertura, el momento óptimo del cultivo debería ser retrasado varias semanas en comparación con el sistema típico basado en labranza, para asegurar tanto el control del malezas como el rendimiento óptimo.